2007
DOI: 10.1021/jf0636465
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Toxicity of Antimicrobial Compounds from Essential Oils

Abstract: Natural antimicrobial compounds perform their action mainly against cell membranes. The aim of this work was to evaluate the interaction, meant as a mechanism of action, of essential oil antimicrobial compounds with the microbial cell envelope. The lipid profiles of Escherichia coli O157:H7, Staphylococcus aureus, Salmonella enterica serovar Typhimurium, Pseudomonas fluorescens, and Brochothrix thermosphacta cells treated with thymol, carvacrol, limonene, eugenol, and cinnamaldehyde have been analyzed by gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
303
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(342 citation statements)
references
References 27 publications
14
303
0
7
Order By: Relevance
“…These results do not confirm the in vitro reported intense antimicrobial activity of cinnamon essential oil against several microorganisms (Unlu et al, 2010). Cinnamaldehyde and eugenol have been shown to inhibit production of the essential enzymes and cause damage to the cell wall of the bacteria in experiments implemented in vitro (Di Pasqua et al, 2007). In general, it has been found that a greater concentration of essential oils is needed to achieve the same effects in foods compared to the in vitro experiments (Smid and Gorris, 1999).…”
Section: Simitzis Bronis Charismiadou Mountzouris and Deligeorgismentioning
confidence: 83%
See 1 more Smart Citation
“…These results do not confirm the in vitro reported intense antimicrobial activity of cinnamon essential oil against several microorganisms (Unlu et al, 2010). Cinnamaldehyde and eugenol have been shown to inhibit production of the essential enzymes and cause damage to the cell wall of the bacteria in experiments implemented in vitro (Di Pasqua et al, 2007). In general, it has been found that a greater concentration of essential oils is needed to achieve the same effects in foods compared to the in vitro experiments (Smid and Gorris, 1999).…”
Section: Simitzis Bronis Charismiadou Mountzouris and Deligeorgismentioning
confidence: 83%
“…It possesses intense antimicrobial (Unlu et al, 2010) and antioxidant (Prasad et al, 2009) properties. Cinnamomum zeylanicum action is mainly attributed to cinnamaldehyde and eugenol, substances that react with lipid and hydroxyl radicals converting them into stable products through their hydrogen-donating ability (Jayaprakasha et al, 2007) and inhibit production of essential enzymes by the bacteria due to the presence of a carbonyl group that binds and inactivates them and/or cause damage to the cell wall of the bacteria (Di Pasqua et al, 2007). Both Gram positive and Gram negative bacteria have been reported to be sensitive to cinnamon oil and cinnamaldehyde in in vitro experiments (Quattara et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Animal trials have also demonstrated the promising effects of EOs against the colonisation and proliferation of Clostridium perfringens (Mitsch et al, 2004;Di Pasqua et al, 2007). The mechanism by which the essential oils exert their antimicrobial activity is poorly understood but the main target appears to be the cell membrane of bacterial cells (Burt, 2004;Di Pasqua et al, 2007).…”
mentioning
confidence: 99%
“…Animal trials have also demonstrated the promising effects of EOs against the colonisation and proliferation of Clostridium perfringens (Mitsch et al, 2004;Di Pasqua et al, 2007). The mechanism by which the essential oils exert their antimicrobial activity is poorly understood but the main target appears to be the cell membrane of bacterial cells (Burt, 2004;Di Pasqua et al, 2007). Because of this, Gramnegative microbes are in general more resistant to the antimicrobial activity of EOs due to the presence of an outer membrane (Kalemba and Kunicka, 2003;Burt, 2004).…”
mentioning
confidence: 99%
“…are already several reports that the essential oils containing alcohol terpenoids act strongly on the cytoplasmic membrane of the microorganisms (DI PASQUA et al, 2007). The essential oil of bay can be used as an antioxidant or natural preservative due to the presence of the terpene alcohols Terpinen-4-ol, and α-Terpineol and phenols, which are also recognized as antimicrobial (BURT;REINDERS, 2004;BAKKALI et al, 2008;MITIC-CULAFIC et al, 2009).…”
Section: Discussionmentioning
confidence: 99%